Inequalities in access to services, basis for policies to reduce the health gap - Juan Pablo Gutiérrez; Ileana Heredia-Pi; María Isidra Hernández-Serrato; Blanca Estela Pelcastre-Villafuerte; Pilar Torres-Pereda; Hortensia Reyes-Morales (Instituto Nacional de Salud Pública, 2019)
Objective. To estimate inequalities in access to health services among Mexican population living in localities of 100 000 or less inhabitants. Materials and methods. Cross-sectional analysis using the National Health and Nutrition Survey 100k 2018 survey data. Access was estimated using health insurance and care for the last health condition. As inequality measure, we estimated the concentration index using an imputation of household per capita income. Results. Among studied population, health insurance was 82.42% and access to care 60.03%. We identified inequalities in both indicators; marginal and pro-poor for insurance and pro-rich for access to care. Conclusion. In Mexico, even within the popuation living in poverty there are inequalities in access to health care. More granular public interventions are needed to address inequalities in an effective way.